The use of extended release bupivacaine with transversus abdominis plane and subcostal anterior quadratus lumborum catheters: A retrospective analysis of a novel technique - Hesham Elsharkawy; Wael Saasouh; Yoon Jeong Cho; Loran Mounir Soliman; Jean-Louis Horn (Wolters Kluwer Medknow Publications, 2020)
Background and Aims: Liposomal bupivacaine (LB) is a formulation of local anesthetic that may exert analgesia over a prolonged period. Anecdotal use of LB suggests benefit and prolonged analgesia when used to supplement infiltration blocks. Our aim was to test the effect of a bolus of LB delivered through a nerve catheter in two types of interfascial plane blocks (transversus abdominis plane and anterior subcostal quadratus lumborum). The effect was evaluated through patient self-reporting of postsurgical pain up to 48 postoperative hours. Material and Methods: Medical records of adult postoperative patients who received LB in a peripheral nerve catheter were followed retrospectively and analysed for pain scores and spread of dermatomal numbness over 48 h following the postoperative dose. A chart review of patients who qualified between June 2015 and March 2017 was performed, and clinical data were obtained from the institutional Perioperative Health Documentation System. Results: Pain scores decreased following LB bolus, and all patients reported efficient block analgesia after bolus injection. Dermatomal numbness decreased gradually and was minimal by 48 h following bolus. Conclusion: LB can be injected through a peripheral nerve catheter to prolong analgesia after catheter removal.